Strategic collaboration for technology-supported development and use of multilingual children’s storybooks in Kenya - Dorcas Wepukhulu (Communicare)
Literacy is critical to achieving the 17 United Nations Sustainable Development Goals but many countries have not achieved globally desirable literacy levels. In this paper I describe a collaborative strategy that the South African Institute for Distance Education (SAIDE) adopted to implement the African Storybook (ASb) in sub-Saharan Africa in response to the shortage of multilingual literacy resources. The paper focuses on Kenya, drawing on my experience as the ASb Partner Development Coordinator and from ASb partner reports. One of the findings is that nationwide literacy programmes may not meet specific literacy needs of children from hard-to-reach communities. Other innovative and unique initiatives need to intervene through a collaborative bottom-up approach. I conclude with some lessons learned, achievements and challenges.